THREE-WAVELENGTH SPECTROPHOTOMETRIC METHOD VALIDATION FOR DETERMINATION OF PREDNISONE TABLET CONTAINING COLORING DYES - Riesta Primaharinastiti; Ika Rizki Helwandi (UPT Penerbitan Universitas Jember)
Asthma is a chronic inflammatory disease that ranksfifth out of the top ten causes of morbidity1. Thedrug therapy commonly used for asthma iscorticosteroid, for example is prednisone2. Thedetermination of the drug in the pharmaceuticaldosage form is very important to ensure its safetyand efficacy. Assay method of prednisone in tabletaccording to Farmakope Indonesia is using HighPerformance Liquid Chromatography (HPLC)3, whichhas good accuracy and precision, but high cost andtook a longer analysis time. These aspects aremaking it less suitable for quality control on a regularbasis. UV-Vis spectrophotometry method could beused as the alternative assay method to determineprednisone in tablet, as prednisone haschromophore and auxochrome groups4. UV-Visspectrophotometry method has shorter analysistimes and lower operating costs while still providinga high precision5. Spectrophotometric method UVVishas been used in previous studies of prednisoneand proven to give good results, for example in thedissolution test6,7. Singh and Verma8 conductedresearch to determine prednisone in tablets basedon the color occurred after prednisone reacted withFeCl3 and K4Fe(CN)6, forming a blueish greensolution. The solution then measured byspectrophotometer giving the analytical wavelengthat 780 nm.The addition of coloring agents in pharmaceuticalpreparations intended to identify products inproduction and distribution, distinguishing the samedose of the drug, preventing product counterfeitingand stability indicators9. However, coloring agent ordye in the formulation could affect the analysisprocess, such as background interfering in theanalytical instrument measurement. In Indonesia,usually we can find prednisone tablet in green color.Dyes used in this study is a mix of light green andtartrazine resulting in a light green color. These dyesalso have a cluster of chromophore and auxochrometo provide absorbance in the UV-Vis spectrumregion. Observing the prednisone solution containing0.1% light green and tartrazine solution at themaximum wavelength of prednisone (238 nm) willgive absorbance of the solution 5% higher.To overcome this problem, the analysis of thespectrophotometry is applied by multi-wavelengthmethod. Dual- or three-wavelengthspectrophotometry methods are very useful toeliminate the absorbance influence of interferingcomponents.a.b.c.Figure 1. Chemical Structure of : a. Prednisone, b. Lightgreen dye, c. TartrazineThe aim of this research was validating threewavelengthspectrophotometry method todetermine prednisone in tablet, containing coloringdyes. The method validation parameters defined inthis research are the